Common data elements for subarachnoid hemorrhage and unruptured intracranial aneurysms: recommendations from the working group on Subject Characteristics - Bijlenga, Philippe; Morita, Akio; Ko, Nerissa U.; Mocco, J.; Morel, Sandrine; Murayama, Yuichi; Wermer, Marieke J. H.; Brown, Robert D.; Etminan, Nima; Hackenberg, Katharina (Neurocritical care, 2019)
The National Institute of Neurological Disorders and Stroke (NINDS) Common Data Elements (CDEs) have been generated to standardize and define terms used by the scientific community. The widespread use of these CDEs promotes harmonized data collection in clinical research. The aim of the NINDS Unruptured Intracranial Aneurysms (UIA) and Subarachnoid Hemorrhage (SAH), and Subject Characteristics working group (WG) was to identify, define, and classify CDEs describing the characteristics of patients diagnosed with an UIA and SAH. Thus, “Participant/Subject characteristics” is a set of factors defining a population of selected individuals and allowing comparisons with a reference population and overtime.MethodsBased on standard terms defined by the United States’ Census Bureau, CDEs previously defined by several (Stroke, Epilepsy and Traumatic Brain Injury) NINDS CDE working groups literature and expert opinion of the WG, the “Participant/Subject characteristics” domain has been defined. A set of 192 CDEs divided in 7 subsections: demographics (8 CDEs), social status (8 CDEs), behavioral status (22 CDEs), family and medical history (144 CDEs), pregnancy and perinatal history (8 CDEs), history data source reliability (3 CDEs), and prior functional status (3 CDEs) was defined. SAH is characterized by 6 core elements, all classified in the “Participant/Subject characteristics” domain. Four exploratory elements out of the 39 for SAH overall are in the “Participant/Subject characteristics” domain, and all remaining 182 CDEs in the “Participant/Subject characteristics” domain are classified as Supplemental-Highly Recommended elements. These CDEs would allow the development of best practice guidelines to standardize the assessment and reporting of observations concerning UIA and SAH.
Gesehen am 01.10.2019